Bird's eyes view of Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (AnCoG. Agency, 2010)
This postcard provides an aerial view of the city of Port of Spain circa early 1900 and shows scant occupation. In the distance the Port of Spain habour can be seen. This used postcard is addressed to Miss V. Osborne of New York and affixed is a one cent United States postage stamp.
Colour: Sepia (print); Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trinidad and Tobago--Aerial Views; Cities and towns--Trinidad and Tobago--Port of Spain; Harbors--Trinidad and Tobago; Dwellings--Trinidad and Tobago